Sabellaria spinulosa (Polychaeta, Annelida) reefs in the Mediterranean Sea: Habitat mapping, dynamics and associated fauna for conservation management. (5th January 2018) - Gravina, Maria Flavia; Cardone, Frine; Bonifazi, Andrea; Bertrandino, Marta Simona; Chimienti, Giovanni; Longo, Caterina; Marzano, Carlotta Nonnis; Moretti, Massimo; Lisco, Stefania; Moretti, Vincenzo; Corriero, Giuseppe; Giangrande, Adriana
Abstract: Bio-constructions by Sabellaria worms play a key functional role in the coastal ecosystems being an engineer organism and for this reason are the object of protection. The most widespread reef building species along Atlantic and Mediterranean coasts is S. alveolata (L.), while the aggregations of S. spinulosa are typically limited to the North Sea coasts. This paper constitutes the first detailed description of unusual large S. spinulosa reefs in the Mediterranean Sea. Defining current health status and evaluating the most important threats and impacts is essential to address conservation needs and design management plans for these large biogenic structures. Present knowledge on Mediterranean reefs of S. alveolata is fragmentary compared to Northeast Atlantic reefs, and concerning S. spinulosa, this paper represents a focal point in the knowledge on Mediterranean reefs of this species. A one-year study on temporal changes in reef structure and associated fauna is reported. The annual cycle of S. spinulosa reef shows a spawning event in winter-early spring, a period of growth and tubes aggregation from spring-early summer to autumn and a degeneration phase in winter. The variations exhibited in density of the worm aggregation and the changes in the reef elevation highlight a decline and regeneration of the structure over a year. The many ecological roles of the S. spinulosa reef were mainly in providing a diversity of microhabitats hosting hard and sandy bottom species, sheltering rare species, and producing biogenic structures able to provide coastal protection. The Mediterranean S. spinulosa reef does not shelter a distinctive associated fauna; however the richness in species composition underscores the importance of the reef as a biodiversity hot-spot. Finally, the roles of the biogenic formations and their important biotic and physical dynamics support the adoption of strategies for conservation of Mediterranean S.spinulosa reefs, according to the aims of the Habitat Directive. Highlights: Sabellaria worms are reef building species usually reported in the Mediterranean Sea. S. alveolata is the most common reef builder species in the Mediterranean Sea. This is the first description of S. spinulosa forming reefs in the Mediterranean Sea. Temporal changes, structure and associated fauna are investigated throughout a year. Strategies for conservation of Mediterranean reefs are required.